Preferences in Between: Moderates in the Catalan Secessionist Conflict - Laia Balcells; Alexander Kuo (Politics and Governance, 2021)
Recent research on territorial preferences focuses on explaining who supports or opposes independence. However, this research overlooks the relevance of an “intermediate” category of citizens who may oppose the territorial status quo of a sub-state territory but not support independence. We use evidence from the critical case of Catalonia to illustrate the relevance of individuals with such preferences for policies and outcomes highly relevant to secessionist conflicts. We present four sets of findings using two-wave panel data from December 2017 (just prior to the December regional elections when Catalan independence was the most salient and contentious issue) and September 2018. First, we find that a sizable plurality within Catalonia supports greater autonomy short of independence; conventional sociodemographic variables explaining support for independence do not strongly account for this preference. Second, such pro-autonomy individuals have considerably more intermediate attitudes regarding the key “on the ground” actions that the Spanish and Catalan governments pursued during the crucial independence drive in 2017. They were more opposed than pro-independence individuals to the unilateral independence efforts, and more opposed than pro-status quo individuals to the Spanish government’s actions to counter these efforts. Third, they expressed emotions around the secessionist conflict similar to pro-status quo individuals. Finally, using an embedded survey experiment, we find that pro-autonomy individuals are more trusting of both the central and regional governments regarding their abiding by an agreement to resolve the conflict, and are less easily “polarized” through priming. Overall, these findings indicate the importance of further analyzing individuals with intermediate territorial views in secessionist conflicts.